The Development of a UN/DOT and ATF Compliant Special Effects Explosives Transportation Packaging/Storage Magazine System - Tassilo Baur (International Society of Explosives Engineers, 2009)
In the motion picture/television industry and to some extent in the entertainment industries in general, there is often a need to use energetic materials to create special effects as part of a production which travels, generally by truck. This can in certain instances create unique compliance challenges given that a production may change its filming location daily or even more often